A Case Study of Hidradenitis Suppurativa. (January 2023) - Bort, Nicole L.
Abstract : Hidradenitis suppurativa (HS) is a complex, chronic, inflammatory skin disease that is often unrecognized or misdiagnosed. Patients frequently present to with painful nodules, inflammatory papules, sinus tracts, and scarring to intertriginous areas seeking care to alleviate symptoms. There is a paucity of information available specifically aimed to educate emergency nurse practitioners on how to recognize, diagnose, and treat this population. The article highlights the main diagnostic criteria and treatment options available for HS patients to help expand disease awareness.